On Constitutional Rights and Political Choices - Takis Tridimas (European Papers, 2019)
(Series Information) European Papers - A Journal on Law and Integration, 2019 4(2), 563-572 | Dialogue | (Table of Contents) I. Introduction. - II. From rights to policies and the interplay between legislation and case law. - III. Ordinary versus constitutional legislation. - IV. Is EU law over-constitutionalised? - V. Conclusion. | (Abstract) The influence of the Court of Justice in the evolution of equality law has been enormous. Interpreting rights provided in EU legislation as mere expressions of pre-existing constitutional rights, as the Court of Justice did in Mangold (judgment of 22 November 2005, case C-144/04 [GC]) and Kücükdeveci (judgment of 19 January 2010, case C-555/07 [GC]), poses challenges to majoritarianism and carries the risk of ossification. Although such mirroring of legislative and constitutional rights has recently been extended beyond the right to equal treatment, whether EU law is over-constitutionalised remains an open question. EU law is remarkably malleable and constitutionalisation coexists with indeterminacy and deference to the legislature.